2020
DOI: 10.1016/j.celrep.2020.107753
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-Driven lncRNA BDNF-AS Induces Endocrine Resistance and Malignant Progression of Breast Cancer through the RNH1/TRIM21/mTOR Cascade

Abstract: Highlights d BDNF-AS induces tamoxifen resistance and malignant progression of breast cancers d BDNF-AS driven by MEF2A-regulated enhancer acts as scaffold of RNH1/TRIM21 d BDNF-AS activates mTOR pathway by abolishing RNH1regulated mTOR mRNA decay

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 48 publications
2
43
1
Order By: Relevance
“…Luminal type is the most common type, accounting for 60%-70% of all breast cancer types [12,13]. TAM is the main treatment drug for Luminal breast cancer, but during the treatment, many patients will develop resistance to TAM, including primary resistance and secondary resistance [14]. MLF1IP plays an integral part in the pathogenesis of breast cancer and may also be associated with the resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Luminal type is the most common type, accounting for 60%-70% of all breast cancer types [12,13]. TAM is the main treatment drug for Luminal breast cancer, but during the treatment, many patients will develop resistance to TAM, including primary resistance and secondary resistance [14]. MLF1IP plays an integral part in the pathogenesis of breast cancer and may also be associated with the resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Xiaorong Lin's study showed that lncRNA BDNF-AS (NR_033312) promoted RNH1 ubiquitination degradation in TRIM21-dependent manner to induce poor outcomes and endocrine therapy resistance of breast cancer, thereby leading to malignant progression. 21 FGD5-AS1 (NR_046252) enhanced nonsmall cell lung cancer cells' proliferation through regulating FGD5-AS1/has-miR-107/FGFRL1 axis, 22 and Fu et al's study also demonstrated that FGD5-AS1 improved cisplatin resistance of non-small cell lung cancer cells through miR-140-5p/WEE1 signaling pathway. 23 Moreover, other malignant tumors have also been reported to correlate with high FGD5-AS1 expression.…”
Section: Discussionmentioning
confidence: 95%
“…LncRNA BDNF-AS was reported to promote breast cancer progression by functioning as a scaffold RNA, supporting RNH1 ubiquitination by the E3 ligase TRIM21 and thus RNH1 degradation. This relieves mTOR mRNA suppression by RNH1 and promotes cell-proliferation associated mTOR signalling and thus cancer progression [89]. In non-small-cell lung cancer cells, lncRNA MetaLnc9 was found to promote cell migration and invasion.…”
Section: Lncrna Involvement In the Ubiquitin-proteasome Systemmentioning
confidence: 99%